Comparison of STSG Donor Site Healing, Dressing with Betamethasone + Polymyxin B Vs Sterile Tulle Dressing Impregnated with 1% Framycetin Sulphate - Ahmed, Shahid; Ahmed, Tahir Masood; Abdul Qadeer; Alam, Khurshid; Majeed, Khawaja Umer; Zafarullah (Indus Journal of Bioscience Research, 2025)
Background: Wound healing at the split-thickness skin graft (STSG) donor site is an important aspect of reconstructive surgery that has been characterized by pain, delayed healing, and complications. Improving patient outcomes is the ultimate goal, and it is critical and possible to do all that is needed to optimize donor site management. Objectives: Experimental objectives to determine the effectiveness of Betamethasone + Polymyxin B dressing to that of sterile tulle dressing soaked in 1% framycetin sulfate in enhancing donor site healing and minimizing complications. Materials and Methods: A prospective randomized controlled trial was carried out for 12 months at CMH Rawalpindi, Pakistan in the duration from 1st November 2023 to 30th November 2024. Out of 100 patients, both groups were formed, and the donor sites were treated with the dressing. Recovery period, reported pain, and adverse outcomes were assessed at 2-week, 4-week, and 6-week intervals. Results: The beta-methadone and polymyxin B dressing was found to have reduced the length of healing time (12 ± 2.5) as compared to framycetin sulfate dressing (16 ± 3.2) p